THE LEVEL OF PREPARATION OF PLAYERS DEPENDS ON MAXIMUM OXYGEN CONSUMPTION (American Journal of Pedagogical and Educational Research, 2023)
Determination and evaluation of the aerobic capacity of football players. Using the PWC170 test, a person's ability to perform physical work is determined by calculating the energy expended on the work performed at a heart rate of 70 beats per minute. As can be seen from the table, the maximum oxygen consumption of the players on average for the group was a good 8 and a satisfactory 7, which indicates an incomplete training of the cardiac reserve.